(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2022)
The initial exogenous feeding is crucial in marine fish larviculture, including tiger grouper (Epinephelus fuscoguttatus). The transition from endogenous to exogenous feed is critical for the survival rate of the early stage of larvae. The exogenous feed can influence digestive enzymes activity and larval growth. This study was aimed to determine the role of initial exogenous feed on digestive enzymes activity and growth in the early stage of tiger grouper larvae. Two treatments tested were feeding larvae with exogenous feed and unfed larvae. The initial exogenous feed given was zooplankton rotifers Brachionus rotundiformis. Parameters observed were digestive enzymes activity, including protease, amylase and lipase; absorption of endogenous feed, and larval growth that consisted of total length and body weight. The result indicated that the digestive enzymes activity of unfed larvae were higher than those of fed larvae at 3 days old. Endogenous feed completely absorbed at 3 days old larvae. The total length of larvae was almost similar between the two treatments. In contrast, the body weight of fed larvae tends to be bigger than that of unfed larvae. Based on the results of this study, the initial exogenous feeding influenced digestive enzymes activity and growth of tiger grouper larvae in the early stage.